Globalization for development : trade, finance, aid, migration, and policy - Goldin, Ian, 1955-; Reinert, Kenneth A.; World Bank. (Washington, DC : World Bank ; Basingstoke ; New York : Palgrave Macmillan, 2007)
This book is essential reading for anyone interested in globalization and development. It provides important new insights and perspectives into how global flows of finance, trade, migrants and ideas shape development and advances the debate by identifying urgently needed policy changes for a more inclusive globalization.
Background and context -- Globalization and poverty -- Trade -- Finance -- Aid -- Migration / with Andrew L. Beath -- Ideas -- Toward a policy agenda.
Includes bibliographical references (p. 265-284) and index.
nmn 09/05/13
Loans
Keywords: International economic relations; Globalization -- Economic aspects; International trade; Capital movements; Economic assistance; Emigration and immigration; Economic policy; Economic development; Poverty -- Developing countries; Globalization -- Economic aspects -- Developing countries